From Synthesis to Characterization of Site-Selective PEGylated Proteins - Belén, Lisandra Herrera; Rangel-Yagui, Carlota de Oliveira; Beltrán Lissabet, Jorge F.; Effer, Brian; Lee-Estevez, Manuel; Pessoa, Adalberto; Castillo, Rodrigo L.; Farías, Jorge G. (Frontiers in Pharmacology, 2019)
Covalent attachment of therapeutic proteins to polyethylene glycol (PEG) is widely used for the improvement of its pharmacokinetic and pharmacological properties, as well as the reduction in reactogenicity and related side effects. This technique named PEGylation has been successfully employed in several approved drugs to treat various diseases, even cancer. Some methods have been developed to obtain PEGylated proteins, both in multiple protein sites or in a selected amino acid residue. This review focuses mainly on traditional and novel examples of chemical and enzymatic methods for site-selective PEGylation, emphasizing in N-terminal PEGylation, that make it possible to obtain products with a high degree of homogeneity and preserve bioactivity. In addition, the main assay methods that can be applied for the characterization of PEGylated molecules in complex biological samples are also summarized in this paper.